Violence, Authority, and Redemption: Examining Two Lear’s Across Time - Nazki, Sameeul Haq (Journal of Humanistic, Management and Social Science Review, 2025)
The themes of violence, power, and redemption in two King Lear and Bond’s Lear are examined in this essay. The study’s goal is to determine how various political and cultural contexts during a given time period influence the interpretation of these themes. Shakespeare’s King Lear, written in the early 17th century, explores human suffering, justice, and the concerns of monarchical power. Edward Bond’s Lear (1971) tackles contemporary issues like war, state power, and social disintegration. The comparison illustrates how a classic text, when viewed in a different historical context, can be interpreted in multiple ways. Thematic comparison and close reading are the techniques used. Violence, power dynamics, and the question of whether the protagonists can be saved are the main topics of the analysis of significant scenes from the plays. The analysis further emphasis how King Lear portrays violence as a natural part of the tragic human condition, frequently associated with human imperfection and fate. Bond, on the other hand, highlights how oppressive and unfair social structures lead to violence. Bond’s play depicts authority as brutal and purposefully constructed, while the original portrays it as sacred. Lear is reinterpreted in the contemporary adaptation as a commentary on the violence and power of the modern world as well as a personal tragedy. This demonstrates how timeless texts can be adapted to appeal to younger audiences. Both the original and Bond’s adaptation analyse the complex struggle between existence and violence as well as the ongoing human experience of dealing with brutality, authority, and violence.